Artificial Intelligence Implementation Strategy to Make It Happen Smart Government Indonesia Gold 2045 - Edo Aryanto; Hijriatul Mabruk; Wiryawan Narendroputro (GoAcademica Research & Publishing, 2023)
The world is currently faced with the challenges of the industrial revolution 4.0 era to realize Smart Government based on internet of things (IOT), big data, augmented reality (AR), cyber security, artificial intelligence (AI), additive manufacturing (AM), simulation, system integration and cloud computing. The application of Artificial Intelligence / AI to public services has been successfully implemented in Singapore and Finland. Meanwhile, in Indonesia there are still challenges that must be faced in implementing AI in public services to realize Smart Government, including information technology (ICT) infrastructure, policies and regulations, rigid bureaucracy, and the ability of human resources to use ICT. So, this research will explain the strategy for implementing AI in Indonesia using the Al-Besher Smart Government Framework based on the results of the SWOT analysis. This research uses qualitative research methods through literature review in the form of primary references, namely journals, articles, news and government performance reports. The research results show that the application of AI to realize Smart Government must carry out the strategy of IoT Enable System, AI Principles/Regulation/IoT Principle, and Shareholders to form a Smart Government Domain which contains 5 (five) Priority Fields for Indonesian Artificial Intelligence for 2020-2045. Apart from that, this research found that to realize Smart Government, administrative reform efforts must be made by forming autonomous organizations, increasing ASN competency by strengthening the meritocracy system, building collaborative governance and establishing a bureaucratic digital transformation law.